TRANSLATION STUDY: HOW CRUCIAL IS CULTURAL KNOWLEDGE FOR STUDENTS AS THE TRANSLATORS? - Djamereng Jumharia; Rusni Rusni (Institut Agama Islam Negeri Palopo, 2018)
This article intends to discuss the importance of teaching cultural knowledge for EFL students in translating text. Translation process is not simply translate word by word but it should also transfer culture together with its language. Since language is a part of culture so both of them always are interrelated each other. Commonly, it will become teacher’ tasks to take his role in translation study, introducing cultural knowledge as part of translation material in lesson plan. The circumstance that students as translator only translate text literally because of their lack of cultural knowledge, therefore they should be enriched with knowledge related to the language and culture. Finally, the crucial factors in translation such as language competence is absolutely needed, the usefulness of cultural competence also act as important as language competence does.